2010
DOI: 10.1117/12.854553
|View full text |Cite
|
Sign up to set email alerts
|

Realization and evaluation of diffractive systems on the back side of silicon solar cells

Abstract: An effective light trapping system is required in silicon solar cells in order to collect a large amount of photons. That is why we focus our investigation on the fabrication and evaluation of two types of optical systems introduced on the back side of solar cells. The aim of these structures is to enhance the light trapping of the long wavelength photons (above 1000 nm). On the one hand, we evaluated a Si/SiO2 linear nanograting; on the other hand, hexagonal nanostructures fabricated with SiO2 nanoparticles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This implies the added assumption that the cladding region is thicker than the coherence length of the incident solar radiation ( SK 1 urn). It has been shown that thicker cladding regions are desirable due to reduced parasitic absorption in the rear reflector [9,12].…”
Section: Cell Typesmentioning
confidence: 99%
“…This implies the added assumption that the cladding region is thicker than the coherence length of the incident solar radiation ( SK 1 urn). It has been shown that thicker cladding regions are desirable due to reduced parasitic absorption in the rear reflector [9,12].…”
Section: Cell Typesmentioning
confidence: 99%
“…Diffraction gratings were first proposed for thin-film solar cells by Sheng et al [2], and later for wafer-based solar cells by Heine and Morf [3]. More recent studies of wafer-based applications can be found in [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption is expected to be higher if the grating structure is transferred to the Al. 36,37 Other approaches with Bragg reflectors have also been proposed to avoid parasitic absorption. 12,13 We find that a separation of the grating and rear reflector is necessary, not only for Al, but also for a less absorbing Ag reflector.…”
Section: B Implementation In Solar Cellsmentioning
confidence: 99%
“…Improper surface passivation has been shown to be a barrier for the successful implementation of back-side diffractive structures in solar cells. 36 The oxide layer used in this model may serve as a back-side passivation layer. In principle, a thin planar optically inactive oxide layer may be inserted between the grating layer and the bulk Si to further reduce surface recombination.…”
Section: B Implementation In Solar Cellsmentioning
confidence: 99%